2012
DOI: 10.1055/s-0031-1298276
|View full text |Cite
|
Sign up to set email alerts
|

RANK, RANKL and OPG Expression in Breast Cancer – Influence on Osseous Metastasis

Abstract: !In women, malignant breast tumours are among the most common malignant diseases in Europe. In advanced breast cancer, the risk of bone metastasis increases to 65-75 %. The discovery of the physiological bone metabolism parameters RANK (receptor activator of nuclear factor-κB), RANKL (receptor activator of nuclear factor-κB ligand) and OPG (osteoprotegerin) as well as their pathophysiological involvement in bone-related diseases is the subject of new therapeutic strategies. The formation of osteolytic bone met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…These factors are known to increase the breast cancer development by regulating patient survival, bypassing apoptosis, invasion, migration and tumor angiogenesis [24]. OPG, TRAIL, and RANKL are significantly higher in tumor epithelial cells from patients with breast cancer than in epithelial cells of non-neoplastic breast tissues [25]. Moreover, the expression of OPG, TRAIL, RANKL, and RANK was significantly higher in spindle-shaped stromal cells from patients with breast cancer than in non-neoplastic tissue stromal cells [25].…”
Section: Opg and Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…These factors are known to increase the breast cancer development by regulating patient survival, bypassing apoptosis, invasion, migration and tumor angiogenesis [24]. OPG, TRAIL, and RANKL are significantly higher in tumor epithelial cells from patients with breast cancer than in epithelial cells of non-neoplastic breast tissues [25]. Moreover, the expression of OPG, TRAIL, RANKL, and RANK was significantly higher in spindle-shaped stromal cells from patients with breast cancer than in non-neoplastic tissue stromal cells [25].…”
Section: Opg and Breast Cancermentioning
confidence: 99%
“…Patients with estrogen receptor-positive (ER+) breast cancer constitute a major clinical population who are at risk for bone metastases [26]. More than 50% of primary breast cancer cells express OPG and RANK, while RANKL could be detected only in 14-60% [25]. OPG is one of the important players of the OPG/ receptor activator of nuclear factor kappa-B (RANK)/RANK ligand (RANKL) triad (Figure 2), and is a secreted member of the TNFR superfamily of proteins [27].…”
Section: Role Of Opg In Metastasismentioning
confidence: 99%
“…Discovery of physiological bone metabolism parameters such as Receptor Activator of Nuclear factor Kappa B (RANK), Receptor Activator of Nuclear factor Kappa Ligand (RANKL) and Osteoprotegerin (OPG) and studies on physiologicaland pathological mechanisms of those provide new targets for the treatment of SANFH. 5,6 MiR-34a can inhibit tumor by participating in proliferation, migration and metastasis of tumor cells. In addition, evidence showed that miR-34a can suppress invasion and metastasis by directly regulating Tgif2 in gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at these separate analyses, the effect on prognosis was only seen with regard to bone metastasisfree survival. Concerning the hypothesis that genetic variants of the RANK/RANKL/OPG system might act through an effect of the skeleton, this result underlines the hypothesis of the RANK pathway being associated specifically with osseous metastases [43].…”
Section: Discussionmentioning
confidence: 65%